Polychlorinated Biphenyl and Organochlorine Pesticide Concentrations in Maternal Mid-Pregnancy Serum Samples: Association with Autism Spectrum Disorder and Intellectual Disability - Lyall, Kristen; Croen, Lisa. A.; Sjödin, Andreas; Yoshida, Cathleen K.; Zerbo, Ousseny; Kharrazi, Martin; Windham, Gayle C. (Environmental health perspectives, 2017)
Polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) are neurodevelopmental toxicants, but few studies have examined associations with autism spectrum disorder (ASD). We aimed to determine whether prenatal exposure to PCBs and OCPs influences offspring risk of ASD and intellectual disability without autism (ID). We conducted a population-based case-control study among Southern California births, including children with ASD ( = 545) meeting (DSM-IV-TR) criteria and ID ( = 181), as well as general population (GP) controls ( = 418). Concentrations of 11 PCB congeners and 2 OCPs measured in banked second-trimester serum samples were compared between the diagnostic groups. Logistic regression was used to calculate crude and adjusted odds ratios (AOR) for associations with ASD, and separately for ID, compared with GP controls, by quartiles of analyte concentrations in primary analyses. Geometric mean levels of several PCB congeners were higher in the ASD group than in the ID and GP groups. ASD risk was elevated for a number of PCB congeners, particularly for the highest vs. lowest quartile of PCB138/158 (AOR = 1.79; 95% CI: 1.10, 2.71) and PCB153 (AOR = 1.82; 95% CI: 1.10, 3.02), and for highest deciles of other congeners in secondary analyses. PCB138/158 was also associated with increased ID (AOR = 2.41; 95% CI: 1.18, 4.91), though no trend was suggested. OCPs were not associated with increased risk of ASD in primary analyses, whereas nonmonotonic increases in risk of ID were found with ´-DDE. Our results suggest higher levels of some organochlorine compounds during pregnancy are associated with ASD and ID. Citation: Lyall K, Croen LA, Sjödin A, Yoshida CK, Zerbo O, Kharrazi M, Windham GC. 2017. Polychlorinated biphenyl and organochlorine pesticide concentrations in maternal mid-pregnancy serum samples: association with autism spectrum disorder and intellectual disability. Environ Health Perspect 125:474-480; http://dx.doi.org/10.1289/EHP277.